2016
DOI: 10.7461/jcen.2016.18.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Gyrus Rectus Resection and Cognitive Impairment after Surgery for Ruptured Anterior Communicating Artery Aneurysms

Abstract: ObjectiveThe gyrus rectus (GR) is known as a non-functional gyrus; hence, its resection is agreed to be a safe procedure frequently practiced to achieve a better surgical view during specific surgeries. This study aimed at comparing the cognitive outcomes following GR resection in patients who underwent surgery for ruptured anterior communicating artery (ACoA) aneurysms.Materials and MethodsFrom 2012 to 2015, 39 patients underwent surgical clipping for ruptured ACoA aneurysms. Mini-mental state examinations (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 19 publications
2
26
0
Order By: Relevance
“…The specific function for left gyrus rectus and right gyrus rectus has not yet been brought to light. However, subgroup analysis showed the negative impact of gyrus rectus resection on language and memory recall categories [19]. Ballmaier M. et al had reported that very significant strong gray matter defects were observed in the gyrus rectus [20].…”
Section: Discussionmentioning
confidence: 99%
“…The specific function for left gyrus rectus and right gyrus rectus has not yet been brought to light. However, subgroup analysis showed the negative impact of gyrus rectus resection on language and memory recall categories [19]. Ballmaier M. et al had reported that very significant strong gray matter defects were observed in the gyrus rectus [20].…”
Section: Discussionmentioning
confidence: 99%
“…The specific function for left gyrus rectus and right gyrus rectus has not yet been brought to light. However, subgroup analysis showed the negative impact of gyrus rectus resection on language and memory recall categories [21]. Ballmaier M. et al had reported that very significant strong gray matter defects were observed in the gyrus rectus [22].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the gyrus rectus may associate with cognitive and memory functions. Joo et al ( 40 ) reported that the gyrus rectus resection had a temporary negative influence on memory recall and language. Qiu et al ( 41 ) showed that the gyrus rectus played a vital role in efficient communications.…”
Section: Discussionmentioning
confidence: 99%